Intranuclear inclusions in macrophages of lizards Lacerta agilis, experimentally infected by acanthocephalan Corynosoma strumosum - V. P. Nikishin; E. M. Skorobrechova (Российский паразитологический журнал, 2019)
The purpose of the research: to study the cell response of non-natural paratenic host and encapsulation process of acanthocephalan Corynosoma strumosum in experiment for further comparison with encapsulation mechanism of this acanthocephalan in natural paratenic host. Materials and methods. Experiments were carried out on 24 lizards Lacerta agilis and one L. viridis. 17 encapsulated acanthocephalans were received from 13 of them. Acanthocephalans with capsules were prepared for electron microscopic analysis according to standard methods and examined in light (semithin sections) and under electron (in ultrathin sections) microscopes. Semithin sections were stained with methylene blue or a mixture of methylene blue and crystal violet. Ultrathin sections were stained with lead citrate. All capsules received in the experiment were investigated with the use of the light microscope; 1,5 and 10 day capsules were examined under electron microscope. Results and discussion. All acanthocephalans studied in this paper including those discovered one and half day after the start of experiment were enclosed in the thick cellular capsule with prevailing mononuclear and multinuclear macrophages. Single electron-dense inclusions of regular rounded shape surrounded by hallo of moderately dense material were found in approximately half of both types of nuclei. Nature of inclusions remained unknown. In the interpretation of results, it is necessary to take into account: 1) the presence of these inclusions in macrophage nuclei only; 2) their strictly ordinary positioning in the nucleus; 3) strictly spherical shape; 4) very high electronic density of their material, that exceeds the density of the nucleolus and chromatin; 5) presence of halo; 6) absence of visible pathological signs in nuclei and cell’s cytoplasm where these inclusions had been found. Their appearance is supposed to be connected with the overactivity of lizard macrophages caused by invasion of a parasitic worm.